Comparison of rectal suppository and intramuscular morphine for management of patients with renal colic referred to the emergency department: A randomized double-blinded controlled trial - Ardestani Zadeh, Arash; Moonesan, Mohammadreza; Taheri, Fatemeh; Arab, Davood; Mokhtari, Tahmineh (Journal of Contemporary Medical Sciences, 2023)
Objectives: To compare the analgesic effects of rectal suppository morphine (RSM) with intramuscular morphine (IMM) in patients suffered from renal colic referred to emergency ward (EW). Methods: In a controlled, randomized, clinical trial, 74/90 patients with renal colic referred to the EW between March 2016 and March 2017 were randomly enrolled into two groups of RSM (10 mg) and IMM (10 mg/mL). Vital signs and severity of pain were recorded at admission time (0), 15, 30 and 60 min after treatment. Results: The results showed that there was a significant decrease in VAS score of RSM group compared to IMM group after 30 and 60 min of administration (P˂0.05). Furthermore, no significant difference was recorded in vital signs, except there was a significant decrease in heart rate (15 and 60 min) and respiratory rate (60 min) of RSM group compared to IMM group (P˂0.05) and no side effects were recorded during the investigation. Conclusion: In conclusion, the use of rectal route of morphine had higher efficiency compared to the IM route of morphine in relieving pain of patients with renal colic. Although, decreased heart and respiratory rates were recorded, the values were in normal range. As well, no major complications were recorded for each method.